TEACHING LISTENING ON NEWS ITEM TEXT USING VIDEO - Akufah, Akufah (ENCOUNTER, 2012)
Indonesian learners who study English as second language still get difficulty in listening because the spoken language and written language is quite different with their mother tongue. This study investigates the effectiveness of teaching listening on news item text using video with the tenth Year Studentsâ of MA MATHOLIâUL HUDA Pucakwangi â Pati in the academic year of 2011/2012. The population of the research was the tenth grade students of MA Matholiâul Huda Pucakwangi Pati. This experimental research is conducted in two classes; the experimental group (X A) and control group (X B) as sample with the data collection methods such as documentation and test. In this research X A was taught by using video, while X B was taught without video (conventional method; recording). The researcher gave listening test to gather the data. The formula that was used to analyze the data was t-test. After the data had been collected by using test, it was found that the pre-test average of the experimental group was 61.81 and control group was 60.14. It was found that t-test was (0.686), whereas the t-table was (1.671) for a = 5%. The t-test score was higher than the t-table (0.686 > 1.671). It was mean that Ho was accepted while Ha was rejected. It could be concluded that both of X A and X B had no differences (homogeneous). While, the post-test average of the experimental group was 74.17 and control group was 70.00. It was found that t-test was (1.898), whereas the t-table was (1.671) for a = 5%. The t-test score was higher than the t-table (1.898 > 1.671). It was mean that Ha was accepted while Ho was rejected. Since t-test score was higher than the t-table, using video was effective medium to improve studentsâ listening on news item texts.